2013
DOI: 10.2478/s13382-013-0161-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mental health in female teachers

Abstract: Objective: Teaching profession is characterised by an above-average rate of psychosomatic and mental health impairment due to work-related stress. The aim of the study was to identify predictors of mental health in female teachers. Material and Methods: A sample of 630 female teachers (average age 47±7 years) participated in a screening diagnostic inventory. Mental health was surveyed with the General Health Questionnaire GHQ-12. The following parameters were measured: specific work conditions (teacher-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 24 publications
5
33
0
14
Order By: Relevance
“…The previous studies have shown positive relationships between headaches and mental illness in females [8] [26]. Another study has shown that those who have tension-type headache tend to have anxiety and depression than those who do not have [27].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The previous studies have shown positive relationships between headaches and mental illness in females [8] [26]. Another study has shown that those who have tension-type headache tend to have anxiety and depression than those who do not have [27].…”
Section: Discussionmentioning
confidence: 98%
“…The previous studies on mental illness in which GHQ-12 was used has reported the relationship between mental illness and subjective fatigue or pain in each body site; head, neck, shoulders, back, and lower back, respectively [8] [22] [23]. Seibt et al has shown that 78% of mentally unhealthy female teachers felt pain in the neck and back and 58% had headaches [8]. Research in the UK has reported a relationship between lower mental states and shoulder pain among workers of five differing job types, including mail carriers and cashiers [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, specific conditions of work organization and physical characteristics of the school setting may not be the most important predictors when evaluating subjective health problems in teachers, such as mental health disorders 14 .…”
Section: Introductionmentioning
confidence: 99%